The awareness of Polish society about bee pollen and its health-promoting properties - preliminary assessment of factors determined bee pollen supplementation in survey-based study - Mirosław Sławiński; Piotr Michał Jarosz; Patryk Jasielski; Michał Zarobkiewicz; Ewelina Wawryk-Gawda; Barbara Jodłowska-Jędrych (Kazimierz Wielki University, 2020)
Introduction: The apiculture is an old and long-established craft. Bee pollen is a flower pollen packed by bees and used as a food source for a hive. Mainly, it consists of simple sugars, protein, fatty acid but also minerals and vitamins. Bee pollen has multiple properties: antioxidative, antineoplastic, antibacterial and much more. It is commonly used by herbalists in treatment of certain medical conditions. Nevertheless, it is unsure whether bee pollen has any health benefits. Purpose: The aim of our study was to assess initially a knowledge of respondents about bee pollen and find out which factors can determine bee pollen supplementation. Materials and methods:  The study was based on an on-line questionnaire, which was created by using Google Forms tool. It consisted of 27 both open and closed questions. Anonymity and resignation opportunity were warranted. The statistical analysis based on questionnaires were elaborated by using R custom script.The Pearson Chi-square test was applied to investigate the relationship between bee pollen usage and: (a) gender, (b) body mass index (BMI) and (c) living area. Results: The study was based on questionnaires given to 511 respondents, 153 of them were represented by men, whereas 358 by women. The 403 respondents gathered what was bee pollen. Bee pollen has been used by 123 persons (24% of respondents). Majority of respondents knew what bee pollen is. However, only one third of this group already used this product in their diet. People who took bee pollen had awareness about the advantages of this dietary supplement. Interestingly, Chi-square test analysis showed that the relationship between bee pollen usage and gender, as well as bee pollen usage and BMI is statistically significant. Contrary, there is no relationship between bee pollen and living area. Conclusions:  Our study has highlighted the issue of this problem area among polish society. Quarter of respondents have ever used bee pollen as a part of their diet. Current results show that polish society has been able to have the knowledge about its beneficial properties, because of their declaration submitted to our survey.